In vitro investigation of the Flusso™ Bypass adapter efficiency upon ventilator circuit disconnect in a clinical simulated environment - Mehri, Rym (Can J Respir Ther, 2020)
RATIONALE: Mechanically ventilated patients must be disconnected from the ventilator during intra-facility transfers. Intentional and accidental circuit disconnections represent a potential hazard to patients (sudden collapse and re-expansion of the alveoli) as well as to clinical staff (exposure to patient’s unfiltered exhalation). Therefore, avoiding abrupt circuit disconnections could better protect the patient’s health and reduce or eliminate contamination risks around clinical staff. OBJECTIVE: The purpose of this in-vitro work was to investigate and evaluate the potential for environmental exposure of Nitric Oxide (NO, as an indicator of any contamination exposure) before and after implementing the novel Flusso™ Bypass adapter during the disconnect procedure of a mechanical ventilator system. METHODS: A mechanical ventilator delivering NO was connected to a breathing simulator with and without the Flusso™ Bypass adapter. The ambient NO concentration was measured when the circuit was briefly disconnected (3 s) during inhalation and exhalation. Both volume and pressure ventilation modes were used. MEASUREMENTS AND MAIN RESULTS: Disconnecting the standard ventilator circuit (pressure-controlled mode) without the Flusso™ Bypass adapter produced higher NO escape to the surroundings (compared with the volume-controlled mode), leading to a longer NO dissipation time. No ambient NO traces were detected when the Flusso™ adapter was used. CONCLUSION: The usage of the Flusso™ adapter drastically decreases the unwanted exposure among clinical staff dealing with potentially hazardous airborne biological aerosols emanating from the circuit. Avoiding abrupt disconnection in the ventilator circuit could reduce lung injuries and alveolar over distension and collapse.